Red‐Emitting Upconverting Nanoparticles for Photodynamic Therapy in Cancer Cells Under Near‐Infrared Excitation. Issue 11 (13th December 2012) - Tian, Gan; Ren, Wenlu; Yan, Liang; Jian, Shan; Gu, Zhanjun; Zhou, Liangjun; Jin, Shan; Yin, Wenyan; Li, Shoujian; Zhao, Yuliang
Abstract Upconverting nanoparticles (UCNPs) have attracted considerable attention as potential photosensitizer carriers for photodynamic therapy (PDT) in deep tissues. In this work, a new and efficient NIR photosensitizing nanoplatform for PDT based on red‐emitting UCNPs is designed. The red emission band matches well with the efficient absorption bands of the widely used commercially available photosensitizers (Ps), benefiting the fluorescence resonance energy transfer (FRET) from UCNPs to the attached photosensitizers and thus efficiently activating them to generate cytotoxic singlet oxygen. Three commonly used photosensitizers, including chlorine e6 (Ce6), zinc phthalocyanine (ZnPc) and methylene blue (MB), are loaded onto the alpha‐cyclodextrin‐modified UCNPs to form Ps@UCNPs complexes that efficiently produce singlet oxygen to kill cancer cells under 980 nm near‐infrared excitation. Moreover, two different kinds of drugs are co‐loaded onto these nanoparticles: chemotherapy drug doxorubicin and PDT agent Ce6. The combinational therapy based on doxorubicin (DOX)‐induced chemotherapy and Ce6‐triggered PDT exhibits higher therapeutic efficacy relative to the individual means for cancer therapy in vitro.